Pengelompokkan Kabupaten/Kota Didasarkan Jaminan Kesehatan di Provinsi Jawa Barat Tahun 2022 - Wiranda, Natasha Bunga; Emeliani, Anggi; Fitriani, Fenny (Mathematics Department, Faculty of Mathematics and Sciences Unisda Lamongan, 2024)
Health is a basic right for every citizen and is one of the country's investments that must be considered. There are still many people we meet who are unable to fulfill their health needs due to limitations in medical expenses. One way that someone prepares themselves to overcome the risk of illness is by registering for insurance such as health insurance. Health insurance is a guarantee provided by the central government, local government, and the private sector to ensure that people have access to health services called health insurance. The results of this study are the grouping of districts / cities in West Java Province based on the variable percentage of the population who have health insurance obtained using multidimensional scaling analysis as many as 4 groups with a STRESS value of 9.9% which is included in the good category